Ambiente laboral y síndrome de Burnout en el personal sanitario del Distrito 07D01 - Preciado Pardo, Anabel Yolanda (My University, 2025)
Burnout syndrome is an increasingly prevalent occupational health problem with critical implications for service quality, staff performance, and institutional sustainability in the health sector. This study aimed to determine the relationship between work environment conditions and burnout syndrome among healthcare personnel in District 07D01, located in El Oro province, Ecuador. A quantitative, descriptive, and correlational study was conducted with a sample of 162 health workers out of a population of 238, using the Maslach Burnout Inventory (MBI) and a psychosocial risk questionnaire. The findings revealed a high prevalence of burnout: 47.5% of participants were at medium risk and 42.6% at high risk, while only 14.8% were classified as low risk. The most affected units were El Guabo, Chilla, District 07D01, and La Peaña. The analysis showed a significant correlation between adverse work conditions—such as excessive workload, lack of recognition, and poor communication—and the development of burnout. As a practical contribution, the study proposes an institutional intervention plan focused on prevention, organizational reform, and psychosocial support to mitigate risk factors, improve the work environment, and enhance staff mental health. It concludes that burnout in District 07D01 is a systemic issue requiring urgent action from district and national health authorities.
El síndrome de burnout constituye un problema creciente de salud ocupacional con implicaciones críticas en la eficiencia, la calidad del servicio y el bienestar del talento humano en el sector sanitario. Esta investigación tuvo como objetivo general determinar la relación entre el ambiente laboral y el síndrome de burnout en el personal sanitario del Distrito 07D01, ubicado en la provincia de El Oro, Ecuador. Se desarrolló un estudio cuantitativo, de tipo descriptivo y correlacional, con una muestra de 162 trabajadores de un total de 238, utilizando como instrumentos el cuestionario Maslach Burnout Inventory (MBI) y una matriz de riesgos psicosociales. Los resultados revelaron una alta prevalencia de burnout: el 47,5 % de los encuestados se encuentra en nivel de riesgo medio y el 42,6 % en riesgo alto, siendo solo el 14,8 % clasificado en nivel bajo. Las unidades operativas con mayor afectación fueron El Guabo, Chilla, Distrito 07D01 y La Peaña. El análisis evidenció una correlación entre las condiciones laborales adversas (sobrecarga, reconocimiento insuficiente, comunicación deficiente) y el desarrollo del síndrome. Como aporte práctico, se propone un plan de intervención institucional con enfoque preventivo, organizacional y psicosocial, orientado a reducir los factores de riesgo, mejorar el clima laboral y fortalecer la salud mental del personal. Se concluye que el burnout en el Distrito 07D01 es un fenómeno estructural que requiere atención prioritaria desde la gestión distrital y nacional en salud.
Keywords: BURNOUT; AMBIENTE LABORAL; SALUD OCUPACIONAL; PERSONAL SANITARIO